Geographic Information System Concept of Operations as a First Step Toward Total Enterprise Asset Management: Metro-North Commuter Railroad Case Study. Issue 1 (2016) - Kizner, Toby; Goldemberg, Michael; Shapiro, Marcia; ten Siethoff, Brian; Wei, Xiaojing; Fogel, David; Kennard, John; Lu, Alex
For this enterprise geographic information system (GIS), Metro-North Commuter Railroad Company adopted the concept of operations (ConOps) process to define goals and objectives, inventory existing GIS assets, analyze data gaps, determine "as is" and "to be" business processes, define staffing and resource requirements and project initiatives, and provide a road map for a comprehensive, companywide GIS deployment. In contrast to the top-down approach typically employed in total enterprise asset management (TEAM) planning, Metro-North used a dynamic grassroots approach, holding 14 workshops, which were attended by 92 employees and were designed to collect GIS goals and objectives. The 122 goals generated from this process were distilled into eight companywide goals. These goals included increased efficiency, data sharing, and decision support. Initiatives were developed for five critical business areas that had the potential for demonstrating how enterprise GIS could help Metro-North accomplish its companywide and broader organizational goals. These pilot applications included visualizing straight-line diagrams, integrating property boundary data, retrieving drawings from the capital programs plan room, visualizing train tracking and delays, and visualizing ridership and demographics. This paper shows how a ConOps process could be used in railroad environments to think through GIS-related issues and to define concrete technology projects that provide tangible benefits to user departments and allow them to manage their assets and business issues. Although the focus of this study was on non-asset-related operations within the railroad, the ConOps process offers a user-centric systems planning approach that could be applied to TEAM efforts within the railroad industry or to the planning of corporate initiatives in any business environment.